The behavioral smart furniture and its relevance to family emotional dynamics - Lina Nageb Fewella (Ain Shams Engineering Journal)
Furniture design could contribute to the emotional and healthy development of the family and society’s well-being. This project utilized family members’ social and behavioral needs to produce interactive furniture that benefited it. A smart residential furniture prototype was produced using local resources, materials, and industrial expertise, revealing its mechanics and challenges. The industrial application aims to produce furniture that helps children with Attention Deficit Hyperactivity Disorder integrate with their family members in daily life. Distance sensors at various heights and positions are utilized to provide illumination responses. The initiative encourages family furniture sharing and hyperactive children to engage with family members. The study offers a comprehensive perspective to designers and manufacturers regarding the potential application of psychological, behavioral, and social design elements in developing a modern, interactive furniture item that contributes to community development, which significantly impacts achieving a sustainable living environment.